Cover Feature: An Isolated Molecule of Iron(II) Phthalocyanin Exhibits Quintet Ground‐State: A Nexus between Theory and Experiment (Chem. Eur. J. 51/2018). Issue 51 (31st August 2018) - Nachtigallová, Dana; Antalík, Andrej; Lo, Rabindranath; Sedlák, Robert; Manna, Debashree; Tuček, Jiří; Ugolotti, Juri; Veis, Libor; Legeza, Örs; Pittner, Jiří; Zbořil, Radek; Hobza, Pavel
Abstract : Determination of the electronic ground state of the isolated iron(II) phthalocyanine (FePc) is still a challenging task. Previous experimental studies performed in the gas phase at high temperature or in the crystalline state assigned the triplet ground state. Multireference CASPT2 and DMRG calculations demonstrate a greater stability of the quintet with respect to the triplet state. This finding is supported by Mössbauer spectroscopy and magnetic measurements of FePc in frozen nonpolar chlorobenzene solvent, which simulates the isolated condition of FePc. More information can be found in the Communication by P. Hobza, R. Zbořil et al. onpage 13413 .